2019
DOI: 10.1088/1361-6579/ab2ba5
|View full text |Cite
|
Sign up to set email alerts
|

Determination of bone sodium (Na) and Na exchange in pig leg using in vivo neutron activation analysis (IVNAA)

Abstract: Objective: The locations of sodium (Na) storage and its exchange mechanisms in the body are not well known. Understanding tissue Na storage and exchange is important for understanding the impact of Na intake, absorption, and retention on human health, especially on the risk of developing chronic diseases. The purpose of this study was to investigate the application of a deuterium-deuterium (DD) neutron generator-based IVNAA system in Na nutrition studies. Approach: The right legs of two live pigs, one on a low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…the absolute concentrations from in vivo measurement may be problematic however the concentrations can still be used for relative comparison). Also, the agrement between in vivo and ex vivo measurement has improved 2 times as compared with our previous study where we found ex vivo measurements to be four times higher primarily due to phantom calibration line 16 . More studies with large sample size are required to confirm the methodology's efficacy for in vivo bone sodium measurement.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…the absolute concentrations from in vivo measurement may be problematic however the concentrations can still be used for relative comparison). Also, the agrement between in vivo and ex vivo measurement has improved 2 times as compared with our previous study where we found ex vivo measurements to be four times higher primarily due to phantom calibration line 16 . More studies with large sample size are required to confirm the methodology's efficacy for in vivo bone sodium measurement.…”
Section: Discussioncontrasting
confidence: 41%
“…The student's t-test at 5% level showed no significant difference in bone sodium of low-sodium and high-sodium diet pigs after 14 days of dietary sodium intervention. In our previous pig study we found Na/Ca bone concentration of 1165 ± 80 ppm in low sodium diet pig while the high sodium diet pig estimated to have a Na/Ca concentration of 1631 ± 111 ppm 16 . The ex-vivo bone sodium concentrations for pig L and pig H were calculated to be 1870(±11) ppm and 2029(±6) ppm.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Finally, Na was also present in the bone tissue in a smaller proportion. It has been shown that among the biological functions of bone tissue is the deposit of minerals, where sodium residing in bone tissue stands out [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%